Neither freedom nor choice : a study of wife abuse in rural Bangladesh - Mannan, M. A. (Md. Abdul) (Dhaka : Forum on Women in Security and International Affairs, 2003)
Study with reference to Comilla and Sirājganj Districts of Bangladesh.
Includes bibliographical references (p. 90-95).
Keywords: Abused wives -- Bangladesh -- Comilla (District) -- Social conditions; Abused wives -- Bangladesh -- Sirājganj (District) -- Social conditions; Rural families -- Bangladesh -- Comilla (District); Rural families -- Bangladesh -- Sirājganj (District)